2014
DOI: 10.1007/s00426-014-0552-x
|View full text |Cite
|
Sign up to set email alerts
|

Inattentional deafness in music

Abstract: While inattentional blindness is a modern classic in attention and perception research, analogous phenomena of inattentional deafness have been widely neglected. We here present the first investigation of inattentional deafness in and with music under controlled experimental conditions. Inattentional deafness in music is defined as the inability to consciously perceive an unexpected musical stimulus when attention is focused on a certain facet of the piece. Participants listened to a modification of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 34 publications
1
35
1
Order By: Relevance
“…Echoing elegantly with the famous inattentional blindness paradigm of Simons and Levins (1997), Dalton and Fraenkel (2012) have shown that participants might experience inattentional deafness by failing to notice the sentence "I am a Gorilla" while attending to an auditory conversation. The occurrence of this phenomenon has also been demonstrated in music listening, whereby some listeners were unable to report a salient electric guitar solo embedded in the XIX th century "Thus Spoke Zarathustra" lyrics poem (Koreimann et al, 2014). Cross-modality interactions are also known to induce inattentional deafness and drive some relevant research on this topic.…”
Section: Introductionmentioning
confidence: 92%
“…Echoing elegantly with the famous inattentional blindness paradigm of Simons and Levins (1997), Dalton and Fraenkel (2012) have shown that participants might experience inattentional deafness by failing to notice the sentence "I am a Gorilla" while attending to an auditory conversation. The occurrence of this phenomenon has also been demonstrated in music listening, whereby some listeners were unable to report a salient electric guitar solo embedded in the XIX th century "Thus Spoke Zarathustra" lyrics poem (Koreimann et al, 2014). Cross-modality interactions are also known to induce inattentional deafness and drive some relevant research on this topic.…”
Section: Introductionmentioning
confidence: 92%
“…Unfortunately, these operational situations are rich of accidents whereby humans failed to notice cues in the visual scene or onboard warning system (Gibb & Gray, ; Murphy & Greene, ). One has to consider that this “inattentional” impairment is not limited to vision and may affect other modalities (Murphy & Dalton, ) such as auditory processing (Koreimann, Gula, & Vitouch, ).…”
Section: Introductionmentioning
confidence: 99%
“…The high cognitive and perceptual loads typical of ATC operations may consume most of attentional resources, thus reducing the remaining attentional capacity for processing unexpected stimuli such as auditory alarms. This failure to perceive auditory stimuli has been called inattentional deafness (Macdonald and Lavie, 2011 ; Koreimann et al, 2014 ). Given the potential impact of inattentional deafness in safety-critical occupations, it is important to understand the factors that promote this phenomenon and to be able to detect its occurrence.…”
Section: Introductionmentioning
confidence: 99%